Use of thermotherapy and tissue culture to free diseased cassava cultivars from cassava mosaic disease. - Acheremu, Kwabena (2015)
A Thesis submitted in Partial fulfillment of the requirement for the award of Master of Science Degree in Agronomy (Plant Breeding).